AUTOMATED SYSTEM FOR CONTINUOUS MICROALGAE CULTIVATION IN PHOTOBIOREACTORS - D’Agostin, D. A. L.; Domene, G. M.; Oliveira, A. S.; Bonfim, M. J. C.; Mariano, A. B. (Revista de Engenharia Térmica, 2017)
The objective of this work was to design a automate system for microalgae cultivation on a continuous modes in laboratory scale and allow its remote monitoring and control. For this, a sensor were developed is able to measure biomass concentration. The concentration sensor used the principle of light scattering, that is, by measuring the turbidity of the culture medium by the use of a set of phototransistor and green led. It presented an mean absolute percentage error of 8.46% during the experiment. A pH, temperature and light sensor were also installed. The control of all the sensors was accomplished by means of an microcontroller. For remote control and monitoring of the controller, a database was designed and implemented on a Raspberry Pi connected to the network. The graphics and data collected are available on an HTML page that allows changes in the control mode of the photobioreactor, for example by changing the dilution rates. The controller was able to operate the photobioreactor in batch mode, as well as to maintain the culture operating in continuous regime. The continuous production of microalgae biomass in a continuous regime showed productivity 74.5% higher than the traditional batch process and 28.2% higher than semicontinuous cultivation.